2011
DOI: 10.1128/aem.00066-11
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the Autotrophic-to-Heterotrophic Biomass Ratio of Picoplankton in Oligotrophic Marine Waters Due to Bottle Enclosure

Abstract: We investigated the effects of bottle enclosure on autotrophic and heterotrophic picoplankton in North and South subtropical Atlantic oligotrophic waters, where the biomass and metabolism of the microbial community are dominated by the picoplankton size class. We measured changes in both autotrophic (Prochlorococcus, Synechococcus, and picoeukaryotes) and heterotrophic picoplankton biomass during three time series experiments and in 16 endpoint experiments over 24 h in light and dark treatments. Our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…In this study, irradiance was not measured at the mooring site during the experiment, preventing the comparison of the light condition between the mesocosm site and the mooring site. It has been reported that long incubation (24 h for NCP and 48 h for CR in this study) in bottles can result in important changes in the abundance, activity, and composition of the community, leading in turn to significant changes in the planktonic metabolism (Pomeroy et al, 1994;Calvo-Díaz et al, 2011). However, unless the irradiance was significantly different between the mesocosm site and the mooring site and/or the artifact of bottle incubation was only significant during phase 2, it is difficult to explain why a similar response was detected for all three NCP datasets during phase 3 but only the response of O 2 -NCP was different from the others during phase 2.…”
Section: Periodmentioning
confidence: 65%
“…In this study, irradiance was not measured at the mooring site during the experiment, preventing the comparison of the light condition between the mesocosm site and the mooring site. It has been reported that long incubation (24 h for NCP and 48 h for CR in this study) in bottles can result in important changes in the abundance, activity, and composition of the community, leading in turn to significant changes in the planktonic metabolism (Pomeroy et al, 1994;Calvo-Díaz et al, 2011). However, unless the irradiance was significantly different between the mesocosm site and the mooring site and/or the artifact of bottle incubation was only significant during phase 2, it is difficult to explain why a similar response was detected for all three NCP datasets during phase 3 but only the response of O 2 -NCP was different from the others during phase 2.…”
Section: Periodmentioning
confidence: 65%
“…Bottle effects are likely enhanced in smaller volume, but I was not able to document dampened bottle effects when increasing the volume from 2.5L to 3.9L (Paper II, Paper III, Paper V) as previously documented (Hammes et al, (2010). This may not come as a surprise given that bottle effects are evident even in large scale (>1000 L) mesocosm incubations (Calvo-Díaz et al, 2011;Hosia et al, 2014;Rahav et al, 2016). Thus the causes of bottle effects remain ambiguous and the problem inevitable.…”
Section: Box 3 | the Bottle Effectmentioning
confidence: 72%
“…This may be due to biofilm forming on the sides of the bottle, changes in substrate availability due to adsorption of cells, carbon or nutrients on glass surfaces, or unintended changes in turbulence patterns, chemistry, or trophic dynamics (Amy and Hiatt, 1989;Calvo-Díaz et al, 2011;Fogg and Calvario-Martinez, 1989). Bottle effects are likely enhanced in smaller volume, but I was not able to document dampened bottle effects when increasing the volume from 2.5L to 3.9L (Paper II, Paper III, Paper V) as previously documented (Hammes et al, (2010).…”
Section: Box 3 | the Bottle Effectmentioning
confidence: 99%
“…Microstructure turbulence was determined by using the same microstructure profiler described for the FAMOSO cruises; processing routines for these data and the calculation of nitrate diffusive fluxes were also similar to those described for the FAMOSO cruises (see above). A description of the methodology used during the TRYNITROP cruise for the determination of nitrate concentration is provided in Mouriño-Carballido et al (2011), and for the analysis of flow cytometry samples in Calvo-Díaz et al (2011).…”
Section: Data Collected During the Trynitrop Cruisementioning
confidence: 99%